Which early 'red flag' symptoms identify children with meningococcal disease in primary care? - Haj-Hassan, T; Thompson, M; Mayon-White, R; Ninis, N; Harnden, A; Smith, L; Perera, R; Mant, D (2011)
BACKGROUND: Symptoms are part of the initial evaluation of children with acute illness, and are often used to help identify those who may have serious infections. Meningococcal disease is a rapidly progressive infection that needs to be recognised early among children presenting to primary care. AIM: To determine the diagnostic value of presenting symptoms in primary care for meningococcal disease. DESIGN OF STUDY: Data on a series of presenting symptoms were collected using a parental symptoms checklist at point of care for children presenting to a GP with acute infection. Symptom frequencies were compared with existing data on the pre-hospital features of 345 children with meningococcal disease. SETTING: UK primary care. METHOD: The study recruited a total of 1212 children aged under 16 years presenting to their GP with an acute illness, of whom 924 had an acute self-limiting infection, including 407 who were reported by parents to be febrile. Symptom frequencies were compared with those reported by parents of 345 children with meningococcal disease. Main outcome measures were diagnostic characteristics of individual symptoms for meningococcal disease. RESULTS: Five symptoms have clinically useful positive likelihood ratios (LR+) for meningococcal disease: confusion (LR+ = 24.2, 95% confidence interval [CI] = 11.5 to 51.3), leg pain (LR+ = 7.6, 95% CI = 4.9 to 11.9), photophobia (LR+ = 6.5, 95% CI = 3.8 to 11.0), rash (LR+ = 5.5, 95% CI = 4.3 to 7.1), and neck pain/stiffness (LR+ = 5.3, 95% CI = 3.5 to 8.3). Cold hands and feet had limited diagnostic value (LR+ = 2.3, 95% CI = 1.9 to 3.0), while headache (LR+ = 1.0, 95% CI = 0.8 to 1.3), and pale colour (LR+ = 0.3, 95% CI = 0.2 to 0.5) did not discriminate meningococcal disease in children. CONCLUSION: This study confirms the diagnostic value of classic 'red flag' symptoms of neck stiffness, rash, and photophobia, but also suggests that the presence of confusion or leg pain in a child with an unexplained acute febrile illness should also usually prompt a face-to-face assessment to exclude meningococcal disease. Telephone triage systems and primary care clinicians should consider these as 'red flags' for serious infection.